Problems and prospects of trade and economic cooperation between Kazakhstan and China - Батырбаев, Кайрат; Nechayeva Елена; Baigondin Ринат (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2023)
The article considers current problems and prospects of trade and economic cooperation between Kazakhstan and China. An important role in the progressive development of the whole complex of relations between the countries is played by trade and economic relations, which in recent years have shown significant progress due to the complementary dynamic development of the economies, geographical proximity, and the implementation of large-scale reforms of both countries in response to the political and economic problems occurring in the world. In this regard, the authors carried out research work on the topic of trade and economic cooperation between Kazakhstan and China. In the course of the study, there were identified key problems of bilateral interaction, and ways of developing contacts between the two countries in the areas of trade, industry, infrastructure, market expansion, and regional cooperation. The analysis shows that the current dynamics of development of trade and economics, investment, energy, transport, and other spheres make it possible to optimistically build further cooperation between the countries. That is why the solution to the problematic issues will make it possible to plan the development of mutually beneficial cooperation in such perspective directions as hydrogen energy, cross-border trade, electronic commerce, tourism, science and technology sphere, and others meeting the requirements of national interests of the two neighboring and friendly states.